Effects of method of cultivation on root density and grain and crop residue yields of sorghum - Tarawali, G.; Mohamed-Saleem, M.A. (1987)
Studies the effect of ridge height on sorghum production and the benefits associated with ridging including increase in yields of grain and residue and root density.